Implementation of Project-Based Learning Model Integrated with Local Wisdom in Language Learning in Elementary School - Wulanda Wulanda; Rani Ardesi Pratiwi; Maulidawati Maulidawati; Al Furqan; Juni Ahyar (Cerdika: Jurnal Ilmiah Indonesia, 2024)
This study aims to analyze the implementation of a project-based learning model integrated with local wisdom in language learning at SD Negeri 10 Muara Batu. This research was conducted using descriptive qualitative approach. The research subjects included 23 grade V students and one language teacher. Data were collected through observation, semi-structured interviews, questionnaires, and documentation. The data obtained will be analyzed through the stages of data collection, categorization, thematic analysis, interpretation, and presentation of results. The results showed that the integration of PjBL with local wisdom significantly improved students' understanding of local culture and encouraged their active involvement in the learning process. The learning stages include the introduction of local wisdom concepts, understanding through discussion, and direct practice in cultural projects. Support from teachers, schools and parents' participation contributed to the successful implementation of this learning model. This approach is also able to increase students' learning motivation and sense of pride in local cultural heritage. The findings indicate that a project-based learning model that integrates local wisdom is effective in enriching learning experiences and shaping students' character who are critical, creative, and have good social skills.